Photoelectrochemical Gas–Electrolyte–Solid Phase Boundary for Hydrogen Production From Water Vapor - Amano, Fumiaki; Shintani, Ayami; Mukohara, Hyosuke; Hwang, Young-Min; Tsurui, Kenyou (Frontiers in Chemistry, 2018)
Hydrogen production from humidity in the ambient air reduces the maintenance costs for sustainable solar-driven water splitting. We report a gas-diffusion porous photoelectrode consisting of tungsten trioxide (WO3) nanoparticles coated with a proton-conducting polymer electrolyte thin film for visible-light-driven photoelectrochemical water vapor splitting. The gas–electrolyte–solid triple phase boundary enhanced not only the incident photon-to-current conversion efficiency (IPCE) of the WO3 photoanode but also the Faraday efficiency (FE) of oxygen evolution in the gas-phase water oxidation process. The IPCE was 7.5% at an applied voltage of 1.2 V under 453 nm blue light irradiation. The FE of hydrogen evolution in the proton exchange membrane photoelectrochemical cell was close to 100%, and the produced hydrogen was separated from the photoanode reaction by the membrane. A comparison of the gas-phase photoelectrochemical reaction with that in liquid-phase aqueous media confirmed the importance of the triple phase boundary for realizing water vapor splitting.